ANALISIS JALUR DALAM FUNGSI PELAYANAN TERHADAP LOYALITAS NASABAH DENGAN PURNA-PELAYANAN SEBAGAI VARIABEL INTERVENING: STUDI KASUS DI BPR PONOROGO - Khuzaini Khuzaini (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
Service and post-service are important factors to create customer’s loyalty, therefore, we should examine the role of service variable to loyalty with post-service variable as intervening variable. Data is collected with total respondents of 155 samples by using purposive sampling method because the total of population is not known. Questionnaire consists of 3 variables that include service with 4 indicators (officer precision, service speed, technology ability and security), post-service with 4 indicators (problem soling, responding speed, correction availability and empathy to complaints) and 3 loyalties (product commitment, information dissemination and returning to buy again).A suitable method to answer above problems is Path Analysis. The result shows that service may have direct influence to loyalty and indirect influence that is from service to post-service as a new intervening to loyalty. Direct influence of service to loyalty that is b1 is 0,727. Indirect influence of service to post-service that is b2 is 0,509 meanwhile from post-service to loyalty, that is b3 is 0,110, therefore indirect influence, that is b2 times b2 is (0,509)*(0,110)=0,05599. Therefore, total influence of service to loyalty is direct influence that is added to indirect influence of 0,727 + 0,05599 = 0,783. It means that the influence of service and post-service is big enough to loyalty i.e. 78,3%, meanwhile the rest of it is 21,7% that is caused by other factor. Based on those results, it can be suggested that a company should give more emphasize to service and post-service because there is evidence that it may cause customer’s loyalty because customer’s loyalty is a very important factor in guaranteeing BPR durability in Ponorogo.